A Systematic Literature Review On The Effects Of Risk Management Practices On The Performance Of Islamic Banking Institutions - Siti Najihah Noory; Shahida Shahimi; Abd. Ghafar Bin Ismail (Penerbit UKM, 2024)
Indexed by MyCite